ABATACEPT - NEW OPPORTUNITIES IN TREATMENT OF JUVENILE IDIOPATHIC ARTHRITIS - E.I. Alexeeva; R.V. Denisova; S.I. Valieva; T.M. Bzarova ("Paediatrician" Publishers LLC, 2009)
The article presents mechanism of action of abatacept, literature data on clinical studies of its effectiveness in adults with rheumatoid arthritis, and results of clinical randomized double-blinded placebo-controlled study of abatacept effectiveness in treatment of different types of juvenile idiopathic arthritis. The analysis of literature data showed that abatacept is new perspective medication for the treatment of rheumatoid arthritis in adults and children.Key words: children, rheumatoid arthritis, abatacept, treatment.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(4):84-89)